Mesoporous polydopamine with built-in plasmonic core: Traceable and NIR triggered delivery of functional proteins. (April 2020) - Wu, Di; Zhou, Jiajing; Chen, Xiaohong; Chen, Yonghao; Hou, Shuai; Qian, Hehe; Zhang, Lifeng; Tang, Guping; Chen, Zhong; Ping, Yuan; Fang, Wenjun; Duan, Hongwei
Abstract: Functional proteins are essential for the regulation of cellular behaviors and have found growing therapeutic uses. However, low bioavailability of active proteins to their intracellular targets has been a long-standing challenge to achieve their full potential for cell reprogramming and disease treatment. Here we report mesoporous polydopamine (mPDA) with a built-in plasmonic nanoparticle core as a multifunctional protein delivery system. The mPDA with a unique combination of large surface area, metal-chelating property, and broad-spectrum photothermal transduction allows efficient loading and near-infrared light-triggered release of functional proteins, while the plasmonic core serves as a photostable tracer and fluorescence quencher, collectively leading to real-time monitoring and active cytosolic release of model proteins. In particular, controlled delivery of cytotoxic ribonuclease A has shown excellent performance in in vivo cancer therapy. The possibility of coating mPDA on a broad range of functional cores, thanks to its universal adhesion, provides opportunities for developing tailored delivery carriers of biologics to overcome intrinsic biological barriers. Graphical abstract: Image 1